Chronic myelomoncytic leukemia: Are we finally solving the identity crisis?. Issue 5 (September 2016) - Nazha, Aziz; Prebet, Thomas; Gore, Steven; Zeidan, Amer M.
Abstract: Chronic myelomonocytic leukemia (CMML) is a unique disease entity with overlap components of both myelodysplastic syndrome and myeloproliferative neoplasms. CMML is a clonal hematopoietic stem cell neoplasm characterized by monocytosis, cytopenias, and extramedullary manifestations such as splenomegaly. The disease is rare and has undergone revisions in its classification. We review the recent classification strategies as well as diagnostic criteria, focusing on the new insights into the genetic alterations and unique pathophysiology of the disease. We also discuss the latest molecular characterization of the disease, including how molecular factors affect current prognostic models. Finally, we focus on available treatment strategies, with a special emphasis on experimental and forthcoming therapies.